Business mathematics for UiTM - Lau, Too Kya (Oxford Fajar, 2019)
This books contain eleven chapters, and is written for easy understanding and appreciation of the subject. Concepts and theories are introduced in a simple and concise manner. Suitable worked examples and diagrams are provided to faciltitate understanding of the concepts and theories.